RESPONSIVITAS KANTOR KEMENTERIAN AGAMA DALAM PELAYANAN PENGURUSAN KENAIKAN PANGKAT FUNGSIONAL GURU DI KABUPATEN KUANTAN SINGINGI TAHUN 2022 - Nabila, Cinta; ', Wazni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
In this study, there are several problematic phenomena that were raised in 2022 in the responsiveness of the Ministry of Religion in the service of managing the promotion of functional teachers in Kuantan Singingi Regency, namely, first, a decrease in the number of functional teacher promotions in the Ministry of Religion of Kuantan Singingi in 2022 from the previous year, there were complaints from teachers regarding the service of managing functional promotions at the Office of the Ministry of Religion of Kuantan Singingi, and there were 36 teachers who made complaints on the questionnaire on the performance of teacher promotion services at the Office of the Ministry of Religion of Kfuantan Singingi. From the above phenomena, the purpose of this study is to determine the responsiveness of the Ministry of Religion in the service of managing the promotion of functional teachers in Kuantan Singingi Regency in 2022. This research is descriptive research with a Pqualitative approach. The types of data are primary data and secondary data, primary data is obtained directly from informants. Meanwhile, secondary data is data that supports or strengthens primary data. Data collection techniques were carried out by means of interviews and documentation. The results of this study indicate that there are complaints from teachers who have not been promoted, namely 36 complaints were obtained from the 2022 teacher promotion questionnaire. These complaints were facilitated in the form of a questionnaire, although still through Google Form which was distributed through the Whatsapp group, but the Kuansing Ministry of Religion should prioritize technological innovation in the form of a complaint website to facilitate data obtained in real time. The Kuansing Ministry of Religion has not fully realized efforts to reduce existing complaints, there is already an SOP in the complaint handling flow, but no points were found for handling complaints by the Kuansing Ministry of Religion, so there has been no transparency of solutions and responses that have been present for these complaints. Keywords: Responsiveness, Public Service, Promotion of Functional Teachers.